An Analysis of the Antecedent Factors Affecting Students’ Enrolment Decisions Across Agricultural Vocational Programs in Malaysia - Ramli, Nurul Azhani; Chinedu, Caleb Chidozie; Dahri, Salma; Owolabi, Babatunde Olawale (Journal of Technical Education and Training, 2024)
Student enrolment in agricultural vocational programs across Malaysia is notably low, posing significant implications for the country's sustainability of human capital, agricultural productivity, and food security. To mitigate these issues, it is essential to understand the relationship between various antecedent factors and students' enrolment decisions in these programs. This research thus investigates the factors that influence students' decisions to enrol in agricultural vocational programs in Malaysia. The study focuses on demographic, sociocultural, socio-psychological, and career-related factors. Data was collected from 308 students from three agricultural vocational colleges and two secondary schools using a cross-sectional survey design. Descriptive and inferential statistics were used to describe participants' demographic characteristics and examine the relationships between these factors and enrolment decisions. The results showed that ethnicity does not significantly influence enrolment, but gender correlates weakly with student enrolment decisions. However, strong correlations were found between sociocultural, socio-psychological, and career-related factors, highlighting the critical roles of family, community norms, personal attitudes, and career prospects in shaping students' decisions to pursue agricultural education. These findings highlight the importance of targeted interventions, inclusive policies, and improved career guidance to attract more students to agricultural vocational programs. The study offers valuable insights for policymakers, educators, and industry stakeholders on addressing the challenges of low enrolment and building a sustainable agricultural workforce for Malaysia.